HARMONISASI DALAM KEANEKARAGAMAN: STUDI SOSIAL BALI, JAWA, DAN MADURA TENTANG AKULTURASI, TOLERANSI, DAN INTEGRITAS DI JEMBRANA SEBAGAI MASYARAKAT MULTIKULTURAL - Made Mahysa Pradnyantari, Ni; Suastika, I Nengah; Budiarta, I Wayan; Dewi, Putu Listya Kyla Candra; Utami, Kadek Sane; Kurniawati, Ni Kadek; Sebayang, Alessandra Gabriella Atetamalem (Program Studi PPKn Universitas Pendidikan Ganesha, 2025)
This study examines the dynamics of social harmony in the multicultural society of Jembrana Regency, Bali, focusing on cultural acculturation, interreligious tolerance, and social integrity among Balinese, Javanese, and Madurese communities. The research aimed to explore how acculturation processes contributed to social cohesion, how tolerance was manifested through interreligious dialogue and the preservation of local traditions, and how social integrity developed within cultural and religious diversity. A qualitative case study was conducted in Loloan Village. Data were collected through in-depth interviews, participatory observations of local traditions and interreligious forums, and document analysis from governmental and academic sources. The findings indicate that social harmony was maintained through shared cultural practices, strengthened interreligious communication, and the formation of an inclusive local identity that transcends ethnic boundaries. These results demonstrate that cultural and religious diversity can be managed constructively to reinforce social cohesion. The harmonization model identified in Jembrana provides strategic insights for managing diversity in other multicultural regions in Indonesia.